Handbook of materials failure analysis with case studies from the chemicals, concrete and power industries - Makhlouf, Abdel Salam Hamdy; Aliofkhazraei, Mahmood (Elsevier, 2016)
Handbook of Materials Failure Analysis: With Case Studies from the Chemicals, Concrete and Power Industries provides an in-depth examination of materials failure in specific situations, a vital component in both developing and engineering new solutions. This handbook covers analysis of materials failure in the chemical, power, and structures arenas, where the failure of a single component can result in devastating consequences and costs. Material defects, mechanical failure as a result of improper design, corrosion, surface fracture, and other failure mechanisms are described in the context of real world case studies involving steam generators, boiler tubes, gas turbine blades, welded structures, chemical conversion reactors and more. This book is an indispensable reference for engineers and scientists studying the mechanisms of failure in these fields.--Provided by publisher.